Clinical case of retrograde endovascular recanalization of chronic coronary occlusion - D. K. Vasiliev; B. A. Rudenko; V. N. Fomin; A. S. Shanoyan; F. B. Shukurov; V. Yu. Vlasov; D. A. Feshchenko; D. S. Chigidinova (Кардиоваскулярная терапия и профилактика)
Coronary chronic occlusion (CCO) occurs in ~20% of cases when coronary angiography is performed in patients with coronary artery disease. According to large observational studies and registries, it is known that most patients with CCO receive only drug therapy. Only 20-22% of patients with CCO undergo surgical myocardial revascularization. Such a low percentage can be explained by a low success rate and a large number of complications during recanalization of CCO at the development stage of endovascular surgery. The accumulation of experience and the improvement of technical equipment has significantly increased the success rate of endovascular revascularization of CCO and reduced the number of complications. More and more scientific evidence has appeared in favor of the recanalization of CCO. It is known that the myocardium in the area of the occluded artery is in ischemia. The presence of a developed system of collateral circulation allows us to ensure sufficient blood flow in the myocardium only at rest, but with a load of collateral blood supply is not enough. Recanalization of CCO can eliminate myocardial ischemia, improve systolic function of the left ventricular myocardium, increase exercise tolerance and improve the quality of life of patients.